Bicultural Attitudes and Psychological Adjustment of Ethnic Minority Youth in Bangladesh - Khaleque, Abdul; Uddin, Muhammad Kamal; Aktar, Rumana; Roy, Kishor; Siddique, Md Nur E Alam (Bangladesh Journal of Psychology, 2024)
This study explored relationships between bicultural attitudes and psychological adjustment of Bangladeshi ethnic-minority youths. The study was conducted on 412 young adults (Mage = 22 years), 40% women and 60% men, from 18 Bangladeshi ethnic subgroups. The Bicultural Attitude Scale (BAS) and Personality Assessment Questionnaire (PAQ) were used as measures. Results presented that 57% of the respondents were biculturally oriented, 42% were uniculturally oriented (39% were oriented toward heritage culture and only 3% toward national culture), and less than 1% were culturally alienated or marginalized. In addition, the results showed that the mean score of importance ratings was significantly higher for the heritage culture than for the national culture. Results also showed a significant negative correlation between the attitude toward heritage culture and the psychological maladjustment of the respondents. The findings further showed that heritage (not national) culture has significant and unique effects on the psychological adjustment of both male and female minority ethnic youth in Bangladesh. Bangladesh Journal of Psychology, Vol. 24, December 2024, pp. 1-22